2022
DOI: 10.1002/ijc.34026
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization analyses of 23 known and suspected risk factors and biomarkers for breast cancer overall and by molecular subtypes

Abstract: Many risk factors have been identified for breast cancer. The potential causality for some of them remains uncertain, and few studies have comprehensively investigated these associations by molecular subtypes. We performed a two-sample Mendelian randomization (MR) study to evaluate potential causal associations of 23 known and suspected risk factors and biomarkers with breast cancer risk overall and by molecular subtypes using data from the Breast Cancer Association Consortium. The inversevariance weighted met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 52 publications
3
24
1
2
Order By: Relevance
“…Age at menopause is an established risk factor for breast cancer in observational studies [45] and MR studies [40], [46]. In our analysis, we observed a strong causal effect on both versions of the overall breast cancer sample, ER+ sample, Luminal A and Luminal B1 subtype (ER+ subtypes), but little evidence of an effect on ER-sample, TNBC and HER-enriched (both ER-subtypes) and Luminal B2.…”
Section: Case Study 4: Age At Menopausesupporting
confidence: 47%
See 1 more Smart Citation
“…Age at menopause is an established risk factor for breast cancer in observational studies [45] and MR studies [40], [46]. In our analysis, we observed a strong causal effect on both versions of the overall breast cancer sample, ER+ sample, Luminal A and Luminal B1 subtype (ER+ subtypes), but little evidence of an effect on ER-sample, TNBC and HER-enriched (both ER-subtypes) and Luminal B2.…”
Section: Case Study 4: Age At Menopausesupporting
confidence: 47%
“…adult and childhood body size and other anthropometric measures [44], [47], [48] reproductive traits [40], sleep traits [49], height [50], IGF-1 [41], smoking [51], lipids [52], [53]), or in MR studies analysing multiple exposure traits as potential risk factors or biomarkers, e.g. identified with a traditional literature search [46] or focusing on a subset of molecular traits [54] [55]. The final set of traits also included many that have robust (FDR corrected) causal estimates of the effect on breast cancer but have not been reported in MR studies before.…”
Section: Discussionmentioning
confidence: 99%
“…Chronotype can be influenced by genetic and environmental factors including cultural and social influences, urban lifestyle, exposure to light, sleep schedule and so on. 44 Given the protective effects of a morning chronotype on several cancer outcomes, [14][15][16]31 strategies that formulate a morning type, like limiting evening screen time and maintaining a regular sleep schedule, should be promoted to reduce the disease burden of these cancers. In addition, chronotype may influence the disease risk via altering diet preference and pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Results when combining findings from previous studies of prostate cancer were 0.95 (95% CI 0.86–1.04) and 0.75 (95% CI 0.54–1.05) respectively. Results of Mendelian randomisation studies in contrast reported adverse effects of genetic variants associated with increased sleep duration and incident oestrogen receptor positive and oestrogen receptor negative breast cancer risk, suggesting that further research using objectively measured metrics of sleep duration, including biological metrics (as opposed to questionnaire data), maybe useful 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%